SPE Annual Technical Conference and Exhibition 2004
DOI: 10.2118/90530-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Non-Darcy and Multiphase Flow Effects in High-Rate, Frac-Pack Gas Completions

Abstract: Hydraulic fracturing combined with gravel packing in high-permeability gas reservoirs (frac-packing, or F&P) is currently considered the most reliable completion technology for offshore Gulf of Mexico (GoM) completions. Such treatments are designed to bypass damage near the wellbore and prevent formation sand production. Despite the relative maturity of this technology, there has been insufficient focus on non-Darcy flow, particularly in the fracture, in F&P wells in the literature. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…This gridding technique we employed was used by others (Lolon et al, 2004;Voneiff et al, 1996) for research work and field studies. The wellbore is in cell (1 Â 1 Â 1) and is operated at constant bottomhole pressure (BHP).…”
Section: Fractured Well Modelmentioning
confidence: 99%
“…This gridding technique we employed was used by others (Lolon et al, 2004;Voneiff et al, 1996) for research work and field studies. The wellbore is in cell (1 Â 1 Â 1) and is operated at constant bottomhole pressure (BHP).…”
Section: Fractured Well Modelmentioning
confidence: 99%
“…Their studies show that high-perforation density of long-penetrating tunnels reduces turbulences. The results of turbulence effects in the perforation tunnels of cased-hole frac-packed (CHFP) gas wells can be found in the studies performed by Lolon et al (2004) and Ouyang (2007). The study by Ouyang (2007) shows that increasing proppant permeability (i.e., using larger gravel for well completion) decreases the turbulence in the perforation tunnels of CHFP wells.…”
Section: Remarksmentioning
confidence: 99%
“…Several studies have been done on turbulence effects in hydraulically fractured gas wells (Wang and Economides, 2004;Gil et al, 2001;Lolon et al, 2004;Kakar et al, 2004;Miskimins et al, 2005;Ouyang, 2007;Huang and Ayoub, 2007;Friedel et al, 2007;Nashawi, 2007) and gas condensate wells Indriati et al, 2002;Ravari and Ibrahim, 2005;Ravari et al, 2007;Mahdiyar et al, 2008). Studies (Gil et al, 2001;Ubani and Evans, 1982) showed that significant turbulence flow can exist in a fracture at any time in the life of a vertically fractured gas well.…”
Section: Turbulence In Hydraulically Fractured Vertical Gas Wellmentioning
confidence: 99%